Airway calibre variation is a major determinant of exhaled nitric oxide's ability to capture asthma control. Issue 2 (17th August 2017) - Michils, Alain; Haccuria, Amaryllis; Michiels, Sebastien; Van Muylem, Alain
Changes in airway calibre have the potential to modify exhaled nitric oxide fraction ( F ENO ) values and could hamper how F ENO captures changes in asthma control. Here, our objective was to assess whether forced expiratory volume in 1 s (FEV1 ) variations alter the ability of F ENO to reflect asthma control. F ENO, asthma control (Asthma Control Questionnaire (ACQ)) and FEV1 were measured at least two times in 527 patients during 1819 pairs of visits. Determinants of F ENO –ACQ discordance probability were evaluated through a logistic regression analysis. The effectiveness of F ENO at capturing either asthma control worsening or improvement between two visits was then assessed by undertaking a stratified receiver operating characteristic curves analysis. When FEV1 and F ENO change in the same direction, the odds of F ENO –ACQ being discordant are multiplied by 3 (p<0.001). The area under the curve values were 0.765 (95% CI 0.713–0.805) (improvement; p<0.001) and 0.769 (95% 0.706–0.810) (worsening; p<0.001) or 0.590 (95% 0.531–0.653) (improvement; p=0.001) and 0.498 (95% 0.416–0.567) (worsening; p=0.482) when FEV1 and F ENO changed in the opposite or same direction, respectively. The manner in which F ENO and FEV1 vary concomitantly when asthma control changes determines the ability of F ENO to capture this change: parallel or opposite changes in FEV1 and F ENO either decrease or increase this ability to capture asthma control changes. Clinicians must take into account FEV 1 changes when using F ENO as a marker of asthma control http://ow.ly/XFmp30c4emj